Dean, Death and the Royal Succession in Scotland c. 1214 - c. 1513 (Boydell, 2024) - Emily Wingfield (Royal Studies Journal, 2025)
Review of Lucinda H.S. Dean, Death and the Royal Succession in Scotland c. 1214 - c. 1513 (Woodbridge: The Boydell Press, 2024)